Respuesta :

Answer:

The given equations are:

1. -6x + 18y = 0

2. 4x - 12y = -20

To apply the linear combination method, we need to eliminate one variable by multiplying each equation by a suitable constant. In this case, if we multiply the first equation by 2 and the second equation by 3, the coefficients of 'y' in both equations will become -36y, allowing us to eliminate 'y'.

After performing the multiplication, we have:

3. -12x + 36y = 0

4. 12x - 36y = -60

Now, when we add equations 3 and 4 together, we get:

-12x + 36y + 12x - 36y = 0 - 60

0 = -60

This resulting equation is 0 = -60, which is not possible. It implies that 0 is not equal to -60, leading us to conclude that the system of equations has no solution.

Therefore, the correct answer is:

The equation has no solution; therefore, the system of equations has no solution.

Step-by-step explanation:

I Do edge too